Perceptions of bias in the selection of international medical graduate residency applicants in Canada - Mathews, Maria; Bourgeault, Ivy; Ryan, Dana (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2023)
Background: In Canada, international medical graduates (IMG) consist of immigrant-IMG and previous Canadian citizens/permanent residents who attended medical school abroad (CSA). CSA are more likely to obtain a post-graduate residency position than immigrant-IMG and previous studies have suggested that the residency selection process favours CSA over immigrant-IMG. This study explored potential sources of bias in the residency program selection process.Methods: We conducted semi-structured interviews with senior administrators of clinical assessment and post-graduate programs across Canada. We asked about perceptions of the background and preparation of CSA and immigrant-IMG, methods applicants use to improve likelihood of obtaining residency positions, and practices that may favour/discourage applicants. Interviews were transcribed and a constant comparative method was employed to identify recurring themes.Results: Of a potential 22 administrators, 12 (54.5%) completed interviews. Five key factors that may provide CSA with an advantage were: reputation of the applicant’s medical school, recency of graduation, ability to complete undergraduate clinical placement in Canada, familiarity with Canadian culture, and interview performance.Conclusions: Although residency programs prioritize equitable selection, they may be constrained by policies designed to promote efficiencies and mitigate medico-legal risks that inadvertently advantage CSA. Identifying the factors behind these potential biases is needed to promote an equitable selection process.